860 views
5 votes
Adam says that the expression 52-3y is equal to 20 when y=2. Explain why Adam's answer is incorrect

User Dooleyo
by
6.0k points

2 Answers

0 votes
When you substitute y with 2, you get 52-3(2). -3(2)=-6.  52-6=46.  46 is not equal to 20.
User Joz
by
5.1k points
4 votes

Answer:

The given expression is


52-3y

If
y=2, then the expression would be equal to


52-3(2)=52-6=46

As you can observe, the expression is equal to 46 not to 20.

Adam's answer is incorrect, because 46 isn't equal to 20, neither the expression, maybe he made a mistake when he did the operations.

User Overhed
by
5.9k points